Evaluation of Different Grades of Granular Activated Carbon Adsorbents for Scavenging Priority Pollutants from Wastewater - Shastri, S.S.; Yenkie, M.K.N. (Asian Journal of Chemistry, 2010)
Increasing environmental awareness and concern have expanded the role of powdered activated carbon (PAC) and granular activated carbon (GAC) adsorbents in scavenging the soluble, chemically stable and biologically non-degradable pollutants from industrial and domestic wastewater. In the present investigation adsorbents prepared from bituminous coal, namely, Filtrasorb-100 (F-100), Filtrasorb-200 (F-200), Filtrasorb-300 (F-300), Filtrasorb-400 (F- 400) and coconut shell based carbons LCK and RRL were evaluated for their efficiency and performance in scavenging pollutants from water. Aqueous solution of m-nitrophenol was used as adsorbate. These GAC samples were subjected to Proximate and Ultimate Analysis, Pore Size Distribution (PSD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Results show that the source material used for preparation of GAC has significant effect on its pore structure, surface texture, resistance to fragmentation and adsorption capacity. Bituminous coal based carbons show high ash content, a rough surface having lot of cracks and irregular protrusions, high pore volume and a widely dispersed pore structure. In contrast, the coconut shell based GAC samples have low ash content, low pore volume and exhibit uniformly dispersed finer pores, which are well connected by solid mass. FTIR spectra show the presence of various carbon-oxygen complexes on the granular activated carbon surface, which makes the surface slightly polar. The effect of physico-chemical parameters associated with the adsorbent on the adsorption equilibrium and adsorbate removal rate was also studied. Adsorption equilibrium and kinetic experiments were carried out in a batch reactor. The obtained results showed that bituminous coal based carbons have higher adsorption capacity for phenols as compared to the coconut shell based carbons.